Effektivisering av tågvinterunderhåll - Nshimirimana,Andre-Michel (2017)
-The purpose of this work is to investigate and identify the most efficacious methods to optimize train maintenance and operations during winter months. The study analyzes scheduled and unscheduled maintenance problems during winter months and considers various options on how to streamline current methods and procedures by identifying key areas and addressing optimization. This study presents proposals on how streamline winter operations and how to reduce time-in-service delays for train operators. To get a better understanding of the systems, many visits have been made to companies within the train maintenance industry. The adopted methodology of this study includes on sight investigative-based research, books, literature reviews and photographic evidence to address the following questions: • How effective are train designs and construction in combating winter weather? • What are the rules and recommendations specified in the TSI for safe train operations? • What preventive or remedial measures would reduce disturbances in the winter traffic? • Whether or not Swedish trains and railway need a deicing system as a standard? Deicing systems and ice-preventive systems are new technologies and literature in this field is very limited. The basis of this work is based on direct surveys with representatives from train maintenance providers, train operators and train consultants, as well as, reports on various de-icing and ice-preventive systems or commonly known as "anti-icing". In summary, the evidence here in will show that the glycerin-based system is efficient in terms of application rates, operating conditions and remote capability. The system has been shown to prevent the formation of ice on critical areas under full operating speeds with an application time of 882ms per train (approximately 100ms per bogie). This is by far the most effective of solutions studied. It is important to mention that at lower speeds (60 km/h to 70 km/h) instead of the speeds that were standard in the investigation (120 km/h to 140 km/h) the RAATS liquid coverage would increase dramatically, as time over the spray arms would increase giving the machine more time to apply the anti-ice liquids as the trains passes. Given the very high speeds trains passes through RAATS machines, it is in my opinion more beneficial if they slow down from 120 km/h to 70 km/h in Gothenburg and Stockholm, during operation, which would increase RAATS liquid coverage significantly with only lead to an approximately 86 second delay. Transport agencies can introduce a speed limit at spray stations and thus eliminate any delays; alternatively, an additional spray arm can be installed to the RAATS (three arms to four arms) there by increasing the volume of liquids to meet the 100km/h speeds. Presently, Nordic GSE method is able to improve on the RAATS three arms liquid coverage, but their liquid applications success is a very low speed (5km/h to 30 km/h). Moreover, Nordic GSE system does not operate on the main line but rather on the sidetracks, without passengers, and the trains have to be taken out of service to be sprayed.
Keywords: tåg; vinterunderhåll; effektivisering